2009
DOI: 10.1021/jp900771g
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Cooling Dynamics in Matrix-Isolated 1,3-Butanediol

Abstract: The complete conformational space of monomeric 1,3-butanediol has been characterized theoretically, and 73 unique stable conformers were found at the MP2/6-311++G(d,p) level. These were classified into nine families whose members share the same heavy atom backbone configurations and differ in the hydrogen atom orientations. The first and third most populated backbone families are governed by the formation of an intramolecular hydrogen bond; however, the second precludes this type of interaction and was frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…37 Based on these predictions, the two conformers should be present in the gaseous sample of 6MOI before the matrix deposition. Since they are separated by a medium-high energy barrier (∼9 kJ mol −1 in the anti → syn direction, see Figure 1), no conformational cooling 5,6,38,39 is expected to occur during the deposition, and therefore both of them should be preserved in both matrices immediately after the deposition, as it has already been confirmed in our previous experiments. Figure 2 shows the mid-infrared spectra of 6MOI isolated in an argon ( Fig.…”
Section: A Gas Phase Conformational Equilibriumsupporting
confidence: 71%
See 1 more Smart Citation
“…37 Based on these predictions, the two conformers should be present in the gaseous sample of 6MOI before the matrix deposition. Since they are separated by a medium-high energy barrier (∼9 kJ mol −1 in the anti → syn direction, see Figure 1), no conformational cooling 5,6,38,39 is expected to occur during the deposition, and therefore both of them should be preserved in both matrices immediately after the deposition, as it has already been confirmed in our previous experiments. Figure 2 shows the mid-infrared spectra of 6MOI isolated in an argon ( Fig.…”
Section: A Gas Phase Conformational Equilibriumsupporting
confidence: 71%
“…[1][2][3][4] Two methodologies are commonly employed to alter the relative abundance of the trapped conformers: annealing of the sample 5,6 or subjecting it to narrowband or broadband radiation of the IR or UV spectral regions. 2,[7][8][9][10][11][12][13][14] In the first case, the population of less stable forms is reduced in favour of the most stable ones, providing that the energy barriers for the isomerizations can be surmounted.…”
Section: Introductionmentioning
confidence: 99%
“…Our calculated properties for the quasi-degenerate conformers I and II and for the next most stable conformer, III, which is >2 kJ mol -1 higher in energy, are summarized in Table S2. FTIR measurements [10] on an annealed, cold 10K matrix isolated 13BD found that the population collapsed to a 1:1 mix of the two thermodynamically most stable conformers.…”
Section: Jet Cooled Experimental Results Showing Mean Homo Electron Pmentioning
confidence: 99%
“…In Figure 1 we compare the two most stable conformers calculated for 13PD [8,9] and those calculated for 13BD. [10,11] The four letter designations used in this literature -g′GG′t and tGG′g -describe the four dihedral angles defining the structures; for brevity we also show and will use an alternative Roman numeral numbering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation